(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article presents the development and validation of a method for assessing the development of motor skills in primary school students. The aim of the study is to create an effective diagnostic tool for objectively assessing the physical fitness and motor skill development of children aged 7–10 years. The developed method includes a set of tests aimed at assessing coordination, strength, endurance, flexibility, and speed. Validation confirmed the reliability and validity of the proposed diagnostic procedures.